The Influence of Digital Changes on Media And Entertainment Business Models: A Case Study of Netflix and Spotify - Pratama, Obi; Narimawati, Umi; Mulyadi (Scimadly Publishing, 2023)
The aim of this research is to investigate the impact of changes in the business models within the entertainment sector. Companies such as Netflix and Spotify were selected as samples to support the theory and conduct real-world practice comparisons. The Business Model Canvas approach, developed by Osterwalder and Pigneur, was used to illustrate modifications in the business model. This study is based on an academic literature review and does not involve empirical investigation. Therefore, practical examples are considered as secondary data. The results of the literature review and responses to the research questions indicate that digital transformation significantly affects the components of the business model. This allows companies in the entertainment and media sector to gain sustainable competitive advantages. This research provides a deeper understanding of how digital transformation impacts a company's business model, particularly in the entertainment and media sector, and underscores the importance of continuous adaptation in response to rapidly changing business environments.